How Do We Develop Positive Health Policy? - David Briggs (ACHSM, 2019)
During the recent Australian Federal election held on the 18th May 2019 much was made by all sides of the political divide about health and health services, much was praised, and more was promised in the name of health policy and improved approaches to health care delivery. Given that the 'quiet Australians' have made their choice and the political angst and dust has diminished, it might be time to return the debate to determine what it was that we all agreed to and where do we go from here.....